Green Economy Based Agriculture Extension in Klaten Regency: A Literature Study on Evaluation and Strategy - Lukman Efendi; Sri Suharsih (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2023)
The agricultural sector has become a potential sector in Klaten Regency. This cannot be separated from the role of agricultural extension workers. Nonetheless, the environment has become a major issue in the development of the agricultural sector and it makes a tradeoff. The aim of this study to provide recommendations for agricultural extension strategies through a green economy approach. This study uses a qualitative approach and supported quantitatiely through weighting and scoring. Data analysis techniques using literature review (library) with SWOT analysis. The agricultural extension program in Klaten Regency has been running in accordance with statutory regulations and technical instructions from the local government. However, the problem that occurs at this time, most of the agricultural extension pay less attention and do not include environmental elements in the agricultural extension process.The agricultural extension model through a green economy-based curriculum is one of the solutions offered in this study. The results of the SWOT analysis in the development of green economy-based agricultural extension agents through the empowerment curriculum is in quadrant I (progressive). In its implementation, a four-actor collaboration model (quadruple helix) is recommended in this study.